This needs to be a journey that we're actually on together'-the introduction of integrated care systems for children and young people in England: a qualitative study of the views of local system stakeholders during winter 2021/22 - Steven Hope; Evgenia Stepanova; Oliver Lloyd-Houldey; Frances Hillier-Brown; Dougal Hargreaves; Dasha Nicholls; Carolyn Summerbell; Russell M. Viner; Zainab Dedat; Emily C. Owen; Stephanie Scott (BMC, 2023)
Abstract Background Integrated care has become a central feature of health system reform worldwide. In England, Integrated Care Systems (ICS) are intended to improve integration across public health, the National Health Service (NHS), education and social care. By April 2021, England had been divided into 42 geographical areas, each tasked with developing local ICS provision. However, it was not clear how ICSs would address the specific needs of children and young people (CYP). This study elicited the views of senior professional stakeholders in the first year of the ICS national roll out, to learn how integrated care for CYP was being implemented within the ICSs and future plans for service provision. Methods A qualitative analysis of in-depth interviews with stakeholders, including healthcare professionals, NHS managers and local authority leaders (n = 25) selected from a diverse sample of ICSs (n = 7) across England, conducted during winter 2021/22. Reflexive thematic analysis involving a collaborative coding approach was used to analyse interview transcripts. Results Four themes were identified, indicating challenges and opportunities for ICSs in relation to the health of CYP: 1) Best start in life (a more holistic approach to health afforded by integrated care); 2) Local and national contexts (tensions between local and national settings and priorities); 3) Funding and planning (instituting innovative, long-term plans using limited existing CYP funding streams); 4) Organisational complexities (integrating the work of diverse organisations). Conclusions The views of stakeholders, provided at the beginning of the journey towards developing local ICS CYP provision, revealed a common aspiration to change focus from provision of acute, largely adult-orientated services towards one with a broader, population health remit, including prevention and early intervention. This would be delivered by integration of a range of local services, including health, education, housing and social care, to set CYP on a life-long path towards improved health and wellbeing. Yet there was an awareness that change would take place over time within existing national policy and funding frameworks, and would require overcoming organisational barriers through further developing local collaborations and partnerships. As ICSs mature, the experiences of stakeholders should continue to be canvassed to identify practical lessons for successful CYP integrated care.